Stylistics and Reflections on Character Education in Abu Nawas's Poem: Humility and Hope for Divine Forgiveness - Diva Sekar Nur Haqim; Rayhan Muhamad Ridwan; Ruly Syaepul Azhar; Rizzaldy Satria Wiwaha; Dadan Rusmana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Abu Nawas, a prominent poet from the Abbasid Dynasty, was renowned for his poems that reflected various themes of life, ranging from praises to rulers to ascetic and religious poetry later in his life. This study aims to analyze stylistics in Arabic literature, particularly the poem Humility and Hope for Divine Forgiveness by Abu Nawas. Stylistics, known in Arabic as ‘ilm al-uslub, is a linguistic and literary study that focuses on the style of language in literary works. This research adopts a qualitative method with a library research approach. Data were collected from various sources, including books, articles, and journals. The findings reveal that the verses in the poem Humility and Hope for Divine Forgiveness by Abu Nawas fall under the category of Uslub Adabi (literary style) since uslub refers to expressions that use language as their medium. This can be observed in the poem's exaggerated praise of Caliph Harun al-Rashid. However, with his humility, Abu Nawas composed poems aimed at criticizing contemporary poets who often imitated ancient poets by subtly introducing themes of ruin. When he recited the poem The Caravan of the Bani Mudhar, considered offensive to the Caliph, Harun al-Rashid became angry and imprisoned him. After his imprisonment, Abu Nawas's poetic themes transformed into more religious ones. This transformation can be seen in his psalms of hope for divine forgiveness, reflecting his spiritual journey toward God. He began contemplating resurrection and life after death, which led him to alter the tone of his prayers and supplications to Allah. Additionally, three character education values are embedded in the poem: humility, honesty, and religiosity.